Care, Control, and the Electroconvulsive Therapy Ritual: Making Sense of Polarized Patient Narratives. (September 2017) - Knight, Fauzia; Ridge, Damien; McShane, Rupert; Ryan, Sara; Griffith, Laura
Despite evidence of short-term effectiveness of ECT (electroconvulsive therapy), both positive and negative patient reports are common. However, research examining these polarized accounts has not adequately elucidated why such divergences occur. We thus sought to examine opposing patient narratives to better understand underlying meanings. Eighteen interviews were conducted with U.K.-based people who had experienced the treatment. Our analysis revealed that the quality of relations with staff, ECT artifacts (e.g., the ECT suite), and perceived outcomes all play a role in divergent accounts. Positive reflections on ECT emerged alongside narratives of trust in staff, comfort with ECT, and perception of sufficient personal control. Conversely, where negative evaluations of ECT predominated, there was anger associated with a lack of control, a belief that ECT made little sense, and was linked to past abuses and/or the unacceptability of side effects. We discuss the implications of our findings for professionals.